2016
DOI: 10.1016/j.neulet.2016.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and valproate prevent methylphenidate-induced mania-like behaviors in the hole board test

Abstract: Manic bipolar is diagnosed by psychomotor agitation, increased goal-directed activity, insomnia, grandiosity, excessive speech, and risky behavior. Animal studies aimed to modeling mania are commonly based in psychostimulants-induced hyperlocomotion. The exploration of other behaviors related with mania is mandatory to investigate this phase of bipolar disorder in animals. In this study, the hole board apparatus was suggested for evaluating mania-like behaviors induced by the psychostimulant methylphenidate. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Work by D'Andrea et al (2015) showed that LC neuronal dysfunction by CREB signaling hyperactivity cause ADHD-like behavior in PI3Kγ conventional knockout (PI3Kγ KO) mice. Since ADHD and mania animal models have overlapped behavioral phenotypes ( Beyer and Freund, 2017 ; Itohara et al, 2015 ), we treated ErbB4-deficient mice with methylphenidate (MHP), a clinical ADHD medication which alleviates hyperactivity of ADHD animal models but aggravates hyperactivity of mania models ( D'Andrea et al, 2015 ; Souza et al, 2016 ; Sumitomo et al, 2018 ). Our results showed that MHP aggravated hyperactivity of ErbB4-deficient ( Erbb4 loxp/loxp + AAV-Cre-GFP) mice ( Figure 5—figure supplement 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Work by D'Andrea et al (2015) showed that LC neuronal dysfunction by CREB signaling hyperactivity cause ADHD-like behavior in PI3Kγ conventional knockout (PI3Kγ KO) mice. Since ADHD and mania animal models have overlapped behavioral phenotypes ( Beyer and Freund, 2017 ; Itohara et al, 2015 ), we treated ErbB4-deficient mice with methylphenidate (MHP), a clinical ADHD medication which alleviates hyperactivity of ADHD animal models but aggravates hyperactivity of mania models ( D'Andrea et al, 2015 ; Souza et al, 2016 ; Sumitomo et al, 2018 ). Our results showed that MHP aggravated hyperactivity of ErbB4-deficient ( Erbb4 loxp/loxp + AAV-Cre-GFP) mice ( Figure 5—figure supplement 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of MPH and ALZ alone and in combination for 4 weeks significantly reduced the body weights, which might be due to loss of appetite and increased locomotor activity associated with MPH administration. [ 17 18 ] On the other hand, the fall in bodyweight of ALZ and A + M treated rats might be as a result of increased energy expenditure due to hyperlocomotion and excessive loss of water through increased frequency of defecation and urination. [ 19 ] However, there were no significant differences in the food and water intake levels.…”
Section: Discussionmentioning
confidence: 99%
“…The doses of VPA employed in our study have been previously reported in the literature to prevent mania-like behavior in rodents. 29,30 All injections were performed between ZT3 and ZT4 (10:00-11:00 AM).…”
Section: Drug Treatmentsmentioning
confidence: 99%